Model usaha BUMDes berbasis pertanian: Sinergi desa dan industri untuk pembangunan ekonomi lokal di Kabupaten Kutai Kartanegara - Pratama, Adnan Putra; Zamroni, Ahmad; Fitrianto, Yuli; Rahman, Mujibu (Journal of Agribusiness Science and Rural Development, 2025)
The establishment of Village-Owned Enterprises (BUMDes) is expected to be one of the driving forces of the rural economy. The potential of the agricultural sector in the village is expected to be optimized by BUMDes to improve the local economy. However, in its implementation, BUMDes found various obstacles both in terms of management and human resource capacity. This study aims to identify the collaboration pattern of BUMDes development that works with industry in order to improve the local economy and identify the challenges faced both internally and externally. The method used is descriptive qualitative with the determination of the location and research respondents purposively. The results obtained in general are that the BUMDes that have been identified have collaborated with several companies or industries in the village such as the mining industry, forestry industry and oil palm plantation industry. The potential of the agricultural sector in the village has partly not been optimized and BUMDes has not been able to process agricultural products in the village into products with more added value. The common challenges faced by BUMDes are maintaining business sustainability and consistency, increasing human resource capacity, and supporting infrastructure. Therefore, involvement is needed from various stakeholder elements such as local government, village government, village communities, and university academics.